PENGARUH KOMUNIKASI BERBASIS KOMPUTER TERHADAP KUALITAS PELAYANAN PERPUSTAKAAN DAN KEPUASAN PEMUSTAKA - Yasin Setiawan; Zulkarnain Zulkarnain; Nurjanah Nurjanah (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2020)
The implementation of self-service (the application of Human Computer Interaction) and SMS-based message machine (the application of Computer Mediated Communication) at Riau University Library, has changed the way of communication in services, changed infrastructure, and user satisfaction. This study aims to examine the significance of the influence of these two innovations on service quality, as well as user satisfaction at Riau University Library. This quantitative research that using questionnaire instrument was conducted in January to October 2019 with a population of 14,757 people, and a sample of 200 people. The study uses a Structural Equation Modeling approach with LISREL tools. Data analysis uses Confirmatory Factor Analysis, which produces T-values for each correlation tested. The effect between variables is considered significant if the T-values are greater than 1.96 (critical significance value). From the results of the analysis, it was found that the implementation of self-service had a significant effect on service quality (T-values=4.986) and significant on the satisfaction of users (2.875), while the implementation of SMS-based message machines was significant on service quality (2.576), but not significantly on user satisfaction (0.877).